Relationship between influenza and dengue outbreaks, and subsequent bacterial sepsis in French Guiana: a time series analysis - Claire Cropet; Philippe Abboud; Emilie Mosnier; Loïc Epelboin; Félix Djossou; Ward Schroeten; Milko Sobesky; Mathieu Nacher (SAGE Publishing, 2021)
Background: Influenza has been shown to increase the risk for severe bacterial infection, in the tropics the seasonality of influenza epidemics is less marked and this may not be the case. Dengue is often followed by prolonged asthenia and some physicians hypothesized increased susceptibility to infections based on anecdotal observations. Methods: Time series of influenza and dengue surveillance were confronted with bacterial sepsis admissions to test the hypotheses. Monthly surveillance data on influenza and dengue and aggregated sepsis data in Cayenne hospital were matched between 24/10/2007 and 27/09/2016. An ARIMA (1,0,1) model was used. Results: The series of the number of monthly cases of sepsis was positively associated with the monthly number of cases of influenza at time t  (β=0.001, p=0.0359). Forecasts were imperfectly correlated with sepsis since influenza is not the only risk factor for sepsis. None of the ARIMA models showed a significant link between the dengue series and the sepsis series.  Conclusions: There was thus no link between dengue epidemics and sepsis but it was estimated that for every 1,000 cases of flu there was one additional case of sepsis. In this tropical setting, influenza was highly seasonal, and improved vaccination coverage could have benefits on sepsis.